On teacher beliefs, self-identity and the stages of professional development - Gabrys-Barker, Danuta (Linguarum Arena, 2018)
This article describes teachers as a professional group, focusing on preservice teachers and refining their profiles on the basis of the studies carried out in educational research. Personality as a major contributor to beliefs and teacher presence in the classroom in a more general sense help to building teacher identity over the period of first becoming and then being a fully-functioning classroom practitioner. Teacher self-concept and identity are developmental in nature and undergo constant fluctuations. They make for the success and/or failure, enthusiasm or burnout of every individual teacher, irrespective of his/her teaching contexts. New teachers who enter classrooms for the first time do not enter them empty-handed. They hold beliefs which have various origins and enjoy varying degrees of sustainability over time and the experiences they encounter. These are discussed here, both theoretically and by means of illustrative studies. When considering teachers over their whole careers, clear developmental stages can be distinguished. These are shown in the form of different models presented in the literature on teacher training and development. The article concludes with a brief description of pre-service teachers` profiles.